Clinical trials of yeast-derived β-(1,3) glucan in children: effects on innate immunity - Richter, Josef; Svozil, Vladimir; Král, Vlastimil; Dobiášová, Lucie Rajnohová; Stiborová, Ivana; Vetvicka, Vaclav (Annals of Translational Medicine, 2014)
Background: The role of glucan in the stimulation of immune reactions is well established. In our report, we focused on the effects of orally administered glucan on nonspecific immunity of children with chronic respiratory problems. Materials and methods: We measured the levels of albumin, lysozyme. C-reactive protein (CRP) and calprotectin in the saliva of 60 children ages 8-12 years and evaluated the effects of 30-day treatment with 100 mg/d oral dose of glucan. Results: We found a significant increase in the production of lysozyme, CRP and calprotectin in glucan-treated children. Conclusions: Short-term oral application of natural immunomodulator β-glucan significantly stimulated mucosal immunity of children with chronic respiratory problems.